Osmotic adjustment of sugar beets in response to soil salinity and its influence on stomatal conductance, growth and yield - Katerji N.; van Hoorn I.W.; Hamdy A.; Mastrorilli M.; Mou Karzel E. (Mediterranean crop responses to water and soil salinity: Eco-physiological and agronomic analyses, 2002)
Sugar beets were grown in tanks filled with loam and clay, and were irrigated with waters of three different levels of salinity. Osmotic adjustment was determined by analyzing the pressure-volume curves at three growth stages. Sugar beets showed osmotic adjustment in two ways: with their phenological development and towards salinity. Owing to the latter adjustment sugar beets are able to maintain the turgor potential at the same value for lower values of the leaf water potential, to maintain stomatal conductance and photosynthesis and finally their production under severe water stress. Salinity affected the pre-dawn leaf water potential, stomatal conductance and evapotranspiration on both soils, but leaf area and yield only on loam. Soil texture affected stomatal conductance, evapotranspiration, leaf area and yields. As the latter was about 35 percent lower on clay, whereas the evapotranspiration decreased 10 to 15 percent, the water use efficiency was about 25 percent lower on clay compared with loam.